Prevalence of vitamin D deficiency in type 2 diabetics and its association with glycemic control (Journal of Fatima Jinnah Medical University, 2021)
Background: Optimal glycaemic control in type 2 diabetics is of utmost importance in preventing the complications of diabetes which lead to increased morbidity and mortality related to the disease. Some studies have shown that vitamin D deficiency was prevalent in type 2 diabetic patients and was associated with poor glycaemic control. This study aimed to determine the vitamin D3 levels in type 2 diabetic patients and its association with glycaemic control.Patients and methods: This cross sectional study was carried out in the outdoor department of Medical Unit II of Sir Ganga Ram Hospital/Fatima Jinnah Medical University Lahore from Feb 10, 2019 to May 9, 2019. A total of 45 cases of type 2 diabetes mellitus were enrolled in this study after taking informed consent from them. Demographic details (name, age, gender, including duration of diabetes) were obtained and blood sample were taken for HbA1c and 25-OH vitamin D3 levels. Vitamin D deficiency was diagnosed by taking serum level
Keywords: Type 2 Diabetes Mellitus; Vitamin D Levels; HbA1C concentration